A Chromosome Level Genome Assembly of a Winter Turnip Rape (Brassica rapa L.) to Explore the Genetic Basis of Cold Tolerance - Wu, Junyan; Xu, Xin-Dong; Liu, Lijun; Ma, Li; Pu, Yuanyuan; Wang, Wangtian; Hua, Xue-Yang; Song, Jia-Ming; Liu, Kede; Lu, Guangyuan; Fang, Yan; Li, Xuecai; et al. (Frontiers in Plant Science, 2022)
Winter rapeseed (Brassica rapa L.) is an important overwintering oilseed crop that is widely planted in the northwest of China and suffers chronic low temperatures in winter. So the cold stress becomes one of the major constraints that limit its production. The currently existing genomes limit the understanding of the cold-tolerant genetic basis of rapeseed. Here we assembled a high-quality long-read genome of B. rapa ‘Longyou-7’ cultivar, which has a cold-tolerant phenotype, and constructed a graph-based pan-genome to detect the structural variations within homologs of currently reported cold-tolerant related genes in the ‘Longyou-7’ genome, which provides an additional elucidation of the cold-tolerant genetic basis of ‘Longyou-7’ cultivar and promotes the development of cold-tolerant breeding in B. rapa.